Development Of Interactive Learning Media Based On Articulate Storyline 3 In Accounting Subjects To Increase Student Learning Motivation In High School - Raymundus Allan Nuari Putra Pratama; Sukirno Sukirno (Global Management: International Journal of Management Science and Entrepreneurship, 2024)
The objectives of this research are: (1) Producing interactive learning media based on articulate storyline 3 in high school accounting learning subjects. (2) Producinh interactive learning media based on articulate storyline 3 which is feasible in learning high school accounting. (3) Knowing the effectiveness of interactive media development based on articulate storyline 3 in high school accounting subjects in increasing students' learning motivation.The type of the research used is research and development with the ADDIE model. The media trial design used a nonequivalent control group experimental design. The feasibility of the product was tested by media experts, material experts, learning practitioners namely teachers, and media users namely students. The media was tested on the research subjects, namely students of class XII IPS 3 SMA N 1 Seyegan. Data collection was carried out by using observation, interviews, and questionnaires. The data collection instruments used interview guidelines, expert validation questionnaire, material validation questionnaire, teacher response questionnaire, student response questionnaire, and student motivation questionnaire. The feasibility of the learning media produced was analysed by using 4 scales, namely very feasible, feasible, inappropriate, and very inappropriate. The results of the study show: (1) Interactive learning learning media based on Articulate Storyline 3 has been successfully developed to increase students‘ learning motivation in high school; (2) Interactive learning learning media based on Articulate Storyline 3 is considered feasible by media experts with a score of 3.66; material experts with a score of 3.47; teacher practitioners 3.65; and students 3.38; (3) Based on the difference in gain score of the experimental group (0.61) from the control which is (0.45), learning media can increase students’ learning motivation.